Understanding the Links between Coaching, OCB, and Individual Performance among MSME Employees - Nadeak, Multi; Widodo, Adi; Asbari, Masduki; Novitasari, Dewiana; Purwanto, Agus (IJOSMAS, 2021)
This study investigates whether increased attention paid to coaching practices affects performance, while considering the mediating effect of OCB. Data were collected from 170 MSME employees in Jabodetabek using quantitative methods and confirmatory surveys. This study shows that coaching has a positive and significant impact on employee performance, either directly or indirectly through OCB mediation. The results of this study could have significant implications for HR managerial decision making regarding the process of implementing and practicing coaching in MSME organizations. This study also helps MSME HR management to seriously assess HR development investment plans in the form of coaching practices and direct their MSME HR strategic planning.